2016
DOI: 10.1186/s13046-016-0414-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of YAP suppresses CML cell proliferation and enhances efficacy of imatinib in vitro and in vivo

Abstract: BackgroundYes-associated protein (YAP), an essential component of Hippo pathway, was identified as an oncoprotein which participated in the progression of various malignancies. However, its role in chronic myeloid leukemia (CML) remains to be further clarified.MethodsThe expression of YAP in CML cells was determined by western blotting. Next, the effects of YAP knockdown and YAP inhibitor on CML cells were evaluated by MTT assay, flow cytometry (FCM) and Wright’s staining. Moreover, K562 induced mice model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 61 publications
2
41
1
Order By: Relevance
“…These results suggest that VP suppresses NB4 cell proliferation. Interestingly, VP has been reported to inhibit cell proliferation and to induce G0/G1 arrest in pancreatic ductal adenocarcinoma cells, hepatocellular carcinoma cells, human retinoblastoma cells, uveal melanoma cells, and chronic granulocyte leukemia cells 20 , 22 , 27 - 29 . Similarly, our FCM data also indicate that cell cycle arrest at the G0/G1 phase is induced by VP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that VP suppresses NB4 cell proliferation. Interestingly, VP has been reported to inhibit cell proliferation and to induce G0/G1 arrest in pancreatic ductal adenocarcinoma cells, hepatocellular carcinoma cells, human retinoblastoma cells, uveal melanoma cells, and chronic granulocyte leukemia cells 20 , 22 , 27 - 29 . Similarly, our FCM data also indicate that cell cycle arrest at the G0/G1 phase is induced by VP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, novel therapeutic targets are necessary to improve the outcomes for patients with APL 27 . YAP functions as an oncoprotein by interacting with TEAD, forming a protein complex critical for the transcription of downstream genes such as c-Myc and Survivin 15 , 22 . Recently, porphyrin family members including VP, hematoporphyrin, and protoporphyrin IX have been found to abrogate the interaction between YAP and TEAD and found function as YAP inhibitors 25 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, porphyrin family members including VP, hematoporphyrin, and protoporphyrin IX have been found to abrogate the interaction between YAP and TEAD and found function as YAP inhibitors 25 , 28 . However, while MST1/2 and YAP1 gene expression have been analyzed in AML 29 , and inhibition of YAP results in a significant anti-leukemia effect in chronic myeloid leukemia 15 , the effect of YAP inhibition in APL remains unclear. Here, we demonstrate the effects of YAP knockdown and the inhibition of YAP function by shRNA and VP, respectively, in HL-60 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have shown that verteporfin without light activation inactivates YAP by inducing conformational changes in YAP protein and enhancing its cytoplasmic retention (Liu-Chittenden et al, 2012;Wang et al, 2016). A number of studies have demonstrated the efficacy of verteporfin as a potent YAP inhibitor and its therapeutic potential for treatment of cancer (Chen et al, 2015;He et al, 2015;Hsu et al, n.d.;Li et al, 2016;Yu et al, 2014). In our study, we treated Sc with verteporfin and analyzed the mRNA levels of a number of genes that are characteristic of functionally mature Sc.…”
Section: Fig 4 Attenuation Of Camp Signaling In Sertoli Cells By Vementioning
confidence: 95%